Toward Fully Multiferroic Van Der Waals Spinfets: Basic Design and Quantum Calculations - Allende-Prieto, S (American Chemical Society, 2024)
Manipulating spin transport enhances the functionality of electronic devices, allowing them to surpass physical constraints related to speed and power. For this reason, the use of van der Waals multiferroics at the interface of heterostructures offers promising prospects for developing high-performance devices, enabling the electrical control of spin information. Our work focuses primarily on a mechanism for multiferroicity in two-dimensional van der Waals materials that stems from an interplay between antiferromagnetism and the breaking of inversion symmetry in certain bilayers. We provide evidence for spin-electrical couplings that include manipulating van der Waals multiferroic edges via external voltages and the subsequent control of spin transport including for fully multiferroic spin field-effect transistors. © 2024 American Chemical Society